Letter from Carl D. Duncan to Patricia Whiting, October 16, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Carl D. Duncan presented Patricia Whiting with a copy of a letter he wrote to Whiting's apartment manager. The letter was prompted by a complaint about Whiting and her roommate. Duncan vouched for their good character in the face of the complaint.